Faktor Adopsi E-Marketing dan Pengaruhnya Terhadap Kinerja Pemasaran UKM Kuliner Kota Bogor - Priyanto, Hery; Najib, Mukhamad; Septiani, Stevia (Universitas Diponegoro, 2020)
The SMEs business is growing rapidly in Bogor City, especially culinary cluster SMEs. Tight competition in the industrial era 4.0 made the culinary cluster SMEs in Bogor City begin to implement a new marketing strategy via internet called e-marketing in order to achieve business growth. The purpose of this study are identify the type of e-marketing most commonly used by culinary cluster SMEs in Bogor City, analyze factors that influence e-marketing adoption by culinary cluster SMES in Bogor City, and analyze the effect of e-marketing adoption on marketing performance SMES of culinary cluster in Bogor City. The method used non-probability sampling with purposive sampling technique, the sample consist of 100 culinary cluster SMEs in Bogor City. The data obtained were processed using Structural Equation Modeling (SEM) with Partial Least Square u approach and using the Smart-PLS 3.0 program. The results of this study indicated social media marketing is the type of e-marketing that is most widely used by culinary cluster SMEs in Bogor City. Relative advantage, top management support, employee capability, competitive environment, and customer pressure were factors that positively and significantly influence the decision to adoptÂ e-marketing of Bogor City culinary cluster SMEs. E-marketing adoption had positive and significant effect on marketing performance of culinary cluster SMEs in Bogor City.